Kalibrasi CT Scan Merk Siemens Type Somatom go.Top di RSUD Banyumas - Agustinus Lise; Diah Rahayu Ningtias; Imam Tri Harsoyo (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
CT Scan calibration is necessary to ensure the accuracy, consistency, and reliability of the medical imaging results used in the diagnosis process. This study aims to find out the calibration procedure and analyze the data of the calibration results of the Siemens SOMATOM go CT Scan. TOP at Banyumas Hospital. The test method refers to the Ministry of Health's CT Scan Testing Working Method No. MK: 056-18, which is the standard in evaluating the performance of CT Scan equipment. The parameters tested included the percentage of tube voltage error (kVp) and the quality of the X-ray beam represented by the Half Value Layer (HVL) value. The results of the measurement of the error percentage at various kVp points show a range of 0.37–0.88%, which is still within the tolerance limit set by the national standard. In addition, the results of the HVL test at voltages of 120 kVp and 140 kVp also showed values that were above the minimum required limit, so that the quality of the X-ray beam was considered to meet the requirements. Based on the overall test and analysis results, the Siemens SOMATOM CT Scan go. TOP is declared feasible, safe, and good to use because all performance parameters of the tool have met applicable standards.